Human rights and education for citizenship, society and identity - Alistair Ross (Educare)
This paper discusses how Universities, who train and educate professionals who work with children and young people, might contribute to the development of a citizenry for the Europe of the future. The paper considers strategies to help young people understand Europe, identify themselves with Europe, and feel that they can help frame the future of Europe. The identity and image of Europe in the minds of young people and their teachers may be very varied. Developing a positive sense and identity with Europe raises issues, particularly around those of European identity, which is only one among many possible identities (regional, national, identities of relationships). Europe is not necessarily the most dominant, and it is unlikely to be so. For young people, the identity of youth more may be more compelling and cohesive. The paper argues that enactive learning of citizenship will naturally involve enactive aspects of citizenship. This will focus on the involvement of young people in establishing rights in their own schools and societies, and extending rights to the third generation. Teaching Citizenship is learning citizenship through active participation – and is something that is done in partnership, educational institutions with and alongside a wide range of social organisations.